Psychometric properties of the original and short Hungarian version of the Iowa infant feeding attitude scale - Renáta Ungváry; András Ittzés; Veronika Bóné; Szabolcs Török (BMC, 2021)
Abstract Background The Iowa Infant Feeding Attitude Scale (IIFAS) is a widely used tool to assess attitudes towards infant feeding. Attitudes towards breastfeeding are one of the main influencing factors of feeding choice and breastfeeding duration. Adaptation of the IIFAS to the Hungarian context provides an opportunity for cross-cultural comparisons and helps to target breastfeeding support interventions. The growing number of shortened scales in various fields of research, demonstrates the necessity to adapt to a changing context of data collection to avoid fatigue and dropout among respondents. However, international comparisons are difficult due to the lack of a consensual shortened form of the scale. The aim of our study was to examine the psychometric properties of the Hungarian version of the IIFAS (IIFAS-H) and propose an 8-item short version that has appropriate construct validity. Methods The original IIFAS was translated into Hungarian and then translated back to English. A cross-sectional study based on an internet survey in 2019 was conducted among 553 mothers whose most recent child's age was between 6 and 36 months. Psychometric properties of the Hungarian IIFAS were determined and compared with international results. In order to obtain a shorter version of the Hungarian scale, we preferably kept those items that are common with other international abbreviated IIFAS versions and deleted items with a corrected item-total correlation or factor loading of less than 0.3, where factor loadings came from a principal component analysis forcing the extraction of one principal component (factor). Results The 17-item IIFAS-H showed good psychometric properties with a Cronbach's alpha of0.73. Further analyses proved that the examined three shortened versions of the IIFAS consisting of 11, 9, and 8 items also showed good properties (Cronbach's alpha = 0.79, 0.79, 0.76, respectively). Conclusions The Hungarian version of the original 17-item long IIFAS proved to be a good measurement tool with good psychometric properties. Based on our analyses, we suggest the use of the 8-item short version (IIFAS-H8) of the scale.